Multiphysics Modeling of an Permanent Magnet Synchronous Machine - MARTIS Claudia (Journal of Electrical and Electronics Engineering, 2012)
This paper analyzes the noise and vibration in PMSMs. There are three types of vibrations in electrical machines: electromagnetic,mechanical and aerodynamic. Electromagnetic force are the main cause of noise and vibration in PMSMs. It is very important to calculate precisely the natural frequencies of the stator system. If oneradial force (which are the main cause for electromagnetic vibration) has the frequency close to the natural frequency of the stator system for the same order of vibrational mode, then this force canproduce dangerous vibration in the stator system. The natural frequencies for a stator system of a PMSM have been calculated. Finally a Structural Analysis has been made , pointing out the radialdisplacement and stress for the chosen PMSM .